2008
DOI: 10.4103/0019-5278.40813
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of plasma butyrylcholinesterase activity and hematological parameters in pesticide sprayers

Abstract: To evaluate the health impact of spraying organophosphorus insecticides (OPs), 34 male sprayers in the mango belt of Malihabad, a small town located 27 km from Lucknow in North India was selected. Plasma butyryl cholinesterase (PBChE) and complete blood count were assessed among sprayers after spraying pesticides and the findings obtained were compared with those determined in a reference group (n = 18). The most common symptoms observed were burning sensation in the eyes (8.82%), itching/skin irritation (23.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
8
18
1
1
Order By: Relevance
“…The depletion of AChE reported in the UAE workers occupationally exposed to OP pesticides correlated well with the frequency of usage and length of use [8], [35][36]. Decreased activity of BChE due to OP exposure in the present study supports the earlier report [37]. In a similar study [38], inhibition of BChE due to OP exposure was reported but results were non-significant.…”
Section: Discussionsupporting
confidence: 86%
“…The depletion of AChE reported in the UAE workers occupationally exposed to OP pesticides correlated well with the frequency of usage and length of use [8], [35][36]. Decreased activity of BChE due to OP exposure in the present study supports the earlier report [37]. In a similar study [38], inhibition of BChE due to OP exposure was reported but results were non-significant.…”
Section: Discussionsupporting
confidence: 86%
“…to be approximately 8 U mL −1 (Rastogi et al, 2008) or 18-67 U mL −1 in another source (Guemei et al, 2001). Interferences were also examined.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Oesterlund et al reported multiple common symptoms of poisoning including skin irritation, headache, extreme tiredness, excessive sweating, blurred vision, and dizziness. 14,18 A study in India by Rastogi et al 19 reported that burning sensation in the eyes/ faces, itching and skin irritation/rash, and dizziness were the most prevalent symptoms among farmers.…”
Section: Discussionmentioning
confidence: 99%